Memory Performance in Patient with Systemic Lupus Erythematosus Using MoCA-Ina in Hasan Sadikin Genneral Hospital Bandung - Safira Anjalia; Paulus Anam Ong; Nur Atik; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2017)
Background: The involvement of neuropsychiatry is reported in 6% to 91% of Systemic Lupus Erythematosus (SLE) patients. It can cause fatal morbidity and mortality. Memory impairment is one of the most common symptoms of neuropsychiatry involvement. This study aims to find out the performance of memory test in SLE patients using Indonesian version of Montreal Cognitive Assessment (MoCA-Ina).Method: This cross sectional study recruited 30 SLE patients. Cognitive abilities and patientâ€™s memory were examined using Indonesian version of Montreal Cognitive Assessment (MoCA-Ina). Cognitive impairment was determined when total MoCA-Ina score was below 26. For memory evaluation, immediate recall or delayed recall impairment was determined when the patient failed in each memory subtests.Results: The mean of total MoCA-Ina score was 24.97 (SDÂ±3.14). Fifty percent of the SLE patients had cognitive impairment, with the domain involved being delayed recall (86.67%), attention (60%), language (56.67%), abstraction (53.33%), and visuo-spatial/ executive function (36.67%). Most patients (86.67%) could completely repeat immediate recall. Whileonly 4 (13.33%) subjects could repeat delayed recall completely without any clue. Of the 26 SLE patients who failed to recall completely, 24 (92.3%) of them succeeded to recall completely after getting clue(s).Conclusion: Memory impairment is the most frequent cognitive impairment in SLE patients, especially in delayed recall. By using the memory subtests of MoCAIna, more than four fifth of patients with SLE was detected having delayed recall memory impairment and almost all of them could recalled completely after getting clue(s). This findings indicated that the finalstep of memory process retrieval in SLE was interrupted while being encoded, but retention pathway were stillintact.Keywords: Systemic Lupus Erythematous, Memory, MoCA-Ina